PENGEMBANGAN KUNCI DETERMINASI KELELAWAR BERINTEGRASI PADA PEMBELAJARAN ANIMALIA KELAS X SMA - Siti Rabiatul Fajri; Sucika Armiani; Nurhasanah Nurhasanah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
The purpose of this study was to develop and test the key of determination of bats in high school class X animalia learning. The research was conducted at Labuapi 1 Public High School in July-August 2019. This research was a ADDIE model of Research and Development (R&D) research. The population of this study was class X. The research sample was taken by cluster random sampling technique. Research data includes the key products of bat determination and product trial data including student responses and teacher responses to learning. The results showed that the study succeeded in making the key to the determination of bats that could be used by students in the class on the subject of animalia biology class X. The key to the determination that was successfully made, was further developed in learning animalia biology. After learning takes place, then analyze the responses of students and teachers to learning by using the key of determination. Students' responses to the use of the determination key obtained the highest average value of 3.54 with good criteria and the lowest average value of 2.33 with no good criteria. The teacher's response to the use of the determination key obtained the highest average value of 4.00 with good criteria and the lowest average value of 3.33 with good criteria.